Edukasi Gizi Seimbang pada Remaja dengan Aplikasi Klik Dokter - Nikmah Ayu Ramadhani Amir; Yuniana Cahyaningrum; Undari Nurkalis; Aem Ismail; Nindita Arum Veibiani (Jurnal LINK, 2026)
During adolescence, nutritional needs increase to support physical growth and cognitive development. However, Indonesian adolescents still face nutritional problems such as malnutrition, obesity, and anemia. The widespread use of smartphones among adolescents provides opportunities for digital health education through applications such as KlikDokter. This community service activity aimed to improve adolescents’ knowledge of balanced nutrition using the KlikDokter application. The activity was conducted through direct health education for students of class 7C at SMP Negeri 18 Surakarta using a pretest and post-test design. The results showed an increase in students’ knowledge after receiving education on adolescent nutrition and the use of the BMI calculator feature in the application. Pretest results showed 17 students in the very good category, 9 in the good category, and 2 in the sufficient category. In the post-test, 22 students were categorized as very good and 6 as good. In conclusion, health education using the KlikDokter application effectively improved adolescents’ knowledge and understanding of balanced nutrition and healthy eating habits because the application is easily accessible and suitable for adolescents’ digital lifestyles.